Eksistensi Batik Sebagai Identitas Nasional di Era Globalisasi - Fadlilah, Naila (Maliki Interdisciplinary Journal, 2025)
Batik is an Indonesian cultural heritage that is rich in aesthetic, philosophical, and historical values, and has been internationally recognized as a symbol of national identity. In the era of globalization, batik faces various challenges in maintaining its existence, but also has great opportunities to develop, especially in the creative economy sector. This study aims to examine the role of batik as a national identity and its preservation and development strategies amidst the dynamics of globalization. The methods used are literature studies and qualitative analysis of the development of batik from cultural and economic aspects. The results of the study show that design innovation that still respects traditional values, preservation of original techniques and motifs, education of the younger generation, and intensive promotion are key factors in maintaining the sustainability of batik. Collaboration between the government, craftsmen, academics, and the community is key to optimizing the role of batik as a symbol of national pride as well as a source of national economic drivers. This study provides strategic recommendations to support the preservation and development of batik in the future.